Community pharmacists’ perceived value on precision medicine, desired training components, and exposure during pharmacy education: Malaysia’s experience - Naimat, Faiza; Fahrni, Mathumalar Loganathan; Purushothaman, Shankar; Abdul Ghani, Mohamad Nizam; Chumnumwat, Supatat; Babar, Zaheer-Ud-Din (Frontiers in Pharmacology, 2022)
Background: Precision medicine beckons new horizons for therapy geared to one’s genetics, lifestyle, and environmental determinants. Understanding of pathology can benefit pharmacists to integrate molecular and clinical diagnostics when providing pharmaceutical care. Our research evaluated the value and appeal of precision medicine to community pharmacists, and training programmes perceived as necessary. Methods: A population-based study was conducted over 10 months across 9 districts in an urban state in Malaysia. A validated and published questionnaire was distributed; questionnaire was also digitally accessible via an online platform during the Covid-19 outbreak. 300 community pharmacists self-administered and returned completed versions (response rate 75%). Five-point Likert scale and multiple-choice responses were analysed using SPSS to assess whether or not exposure through the pharmacy curricula impacted levels of awareness, perception and willingness to pursue precision medicine. Results: Respondents were largely: females (N=196, 65.3%) and practicing community pharmacists for up to 10 years (N=190, 66.3%). Although knowledge levels were moderate (76%), positive perceptions were showcased (94%), while 60% were willing to integrate precision medicine into daily practice. Although 61% did not or do not recall having had prior exposure to pharmacogenomics as part of their pharmacy school curricula, many were willing to acquire knowledge (93%) by undergoing additional training. Desired training included current pharmacogenetic testing available (17%), interpretation of the test results (15%) and ethics (13%). Having 11-20 years of work experience (mean rank = 229.1) versus 31-40 years (mean rank = 201.7) (Z = 3.67, p = 0.019) and exposure during pharmacy education (p=0.038) positively impacted the willingness to integrate precision medicine in daily practice. Conclusion: Community pharmacists were receptive to and valued precision medicine. A relatively high number had prior exposure to concepts through the pharmacy curriculum, and were therefore very willing to adopt precision medicine in their day-to-day practice. With adequate training centred on bioethics, utilising pharmacogenetic testing, and interpretation of the results, community pharmacists will be equipped for the provision of precision medicine services in the foreseeable future. End-users were not directly involved in this study; however, its outcome will be used in programmes that engage and partner with end-users.